Modulation of Inflammation by Extracellular Granzyme A - van Daalen, Kim R.; Reijneveld, Josephine F.; Bovenschen, Niels (Frontiers in Immunology, 2020)
Granzyme A (GrA) has been described as one of the key players in the induction of cell death of neoplastic, foreign or infected cells after granule delivery by cytotoxic cells. In addition, accumulating evidence indicates roles for extracellular GrA in modulating inflammation and inflammatory diseases. This paper aims to explore the literature presenting current knowledge on GrA as an extracellular modulator of inflammation by summarizing i) the presence and role of extracellular GrA in several inflammatory diseases, and ii) the potential molecular mechanisms of extracellular GrA in augmenting inflammation.